A broadband filter based on hybrid spoof surface plasmon and half‐mode substrate integrated waveguide structure. Issue 5 (19th October 2018) - Guan, Dong‐Fang; You, Peng; Yang, Zang‐Biao; Xu, Shen‐Da; Huang, Xianjun; Yong, Shao‐Wei
Abstract: In this article, a novel design way of wideband bandpass filter (BPF) is proposed. A hybrid sharing waveguide based on spoof surface plasmon (SSP) and half‐mode substrate integrated waveguide (HMSIW) is developed. With low‐pass feature of SSP and high‐pass feature of HMSIW, the proposed waveguide is a BPF naturally and the filter bandwidth can be controlled by adjusting parameters easily. A filter sample is fabricated for verification and the measured 3‐dB bandwidth is 46%. The proposed new concept of filter design is attractive and can be used to develop different wideband BPFs.